2015
DOI: 10.1111/coa.12358
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin and bile acids in saliva in patients with laryngopharyngeal reflux – a prospective comparative study

Abstract: The study results show that the levels of total pepsin and bile acids in saliva are significantly higher in patients with LPR than in the controls, thus suggesting this as a useful tool in the diagnosis of LPR and particularly biliary LPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 19 publications
3
105
0
5
Order By: Relevance
“…It is likely that the sensitivity of salivary pepsin testing could be improved by increasing the frequency of sampling and sampling when symptomatic. Previous studies have shown that patients with proximal reflux as defined by oesophageal pH or impedance testing have higher levels of pepsin in their saliva [24,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the sensitivity of salivary pepsin testing could be improved by increasing the frequency of sampling and sampling when symptomatic. Previous studies have shown that patients with proximal reflux as defined by oesophageal pH or impedance testing have higher levels of pepsin in their saliva [24,33].…”
Section: Discussionmentioning
confidence: 99%
“…Pepsin has been identified in the sputum and bronchoalveolar lavage fluid of patients with chronic cough and LPR [6,20], and it has been used to indicate aspiration in patients with lung allografts [21] and the effectiveness of anti-reflux surgery [22]. Salivary pepsin has a moderate sensitivity and specificity for the diagnosis of gastrooesophageal reflux disease in patients with heartburn [23], and its association with scores obtained by clinical diagnostic tools such as the RSI and RFS has been investigated only in smaller studies to date [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Pepsins are major proteolytic enzymes present in the gastric juices produced by the gastric chief cells and hence can only occur in saliva as a result of gastric contents reaching the oral cavity [21]. It appears that gastro-oesophageal reflux disease patients have higher [pepsin] saliva than healthy individuals, possibly due to more frequent or larger volumes of refluxate reaching the oral cavity in the disease condition [22,23]. Pepsin therefore seems an ideal, acute biomarker of reflux events and the authors hypothesise that higher concentrations of pepsin will be found in saliva if the intake of carbonated beverages or other "refluxogenic" food items has caused the gastric contents to reach the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary pepsin has been proposed as a promising biomarker 7,8 . Pepsin is a proteolytic enzyme produced in the stomach, so its presence in the oropharynx and tracheobronchial tree suggests reflux and resultant aspiration.…”
mentioning
confidence: 99%